2014
DOI: 10.1016/j.ajog.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic epidemiology of pelvic organ prolapse: a systematic review

Abstract: Given current evidence supporting a genetic predisposition for pelvic organ prolapse (POP), we conducted a systematic review of published literature on the genetic epidemiology of POP. Inclusion criteria were linkage studies, candidate gene association and genome-wide association studies (GWAS) in adult women published in English and indexed in PubMed through December 2012, with no limit on date of publication. Methodology adhered to the PRISMA guidelines. Data were systematically extracted by two reviewers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 40 publications
(154 reference statements)
2
55
0
6
Order By: Relevance
“…Given how common both childbirth and surgery for pelvic floor disorders are, it is surprising how very little data are present about how the dose and timing of physical activity during these potentially vulnerable times impact the pelvic floor and subsequent pelvic floor disorders. It is also crucial to understand the role physical activity, a potentially modifiable risk factor, plays in women at potentially high genetic risk 82 , women with risk factors for levator ani muscle injury 83 , or, importantly, the substantial minority of women with asymptomatic pelvic organ prolapse. 8486 …”
Section: Future Researchmentioning
confidence: 99%
“…Given how common both childbirth and surgery for pelvic floor disorders are, it is surprising how very little data are present about how the dose and timing of physical activity during these potentially vulnerable times impact the pelvic floor and subsequent pelvic floor disorders. It is also crucial to understand the role physical activity, a potentially modifiable risk factor, plays in women at potentially high genetic risk 82 , women with risk factors for levator ani muscle injury 83 , or, importantly, the substantial minority of women with asymptomatic pelvic organ prolapse. 8486 …”
Section: Future Researchmentioning
confidence: 99%
“…23 Although specific genetic predisposition has not been identified, a systematic review of genetic studies found that collagen type 3 alpha 1 was associated with POP (OR 4.79). 24 …”
Section: Phase I: Predisposing Factors For Pelvic Floor Disordersmentioning
confidence: 99%
“…[43] In the first GWAS for POP, Allen-Brady and colleagues identified six loci (4q21, 8q24, 9q22, 15q11, 20p13, and 21q22) with genome-wide statistical significance in a population of EA women [42]. The second GWAS, undertaken in AA and Hispanic women from the WHI-HT [15], reported several loci with suggestive statistical significance but found no evidence of association for previously reported loci.…”
Section: Discussionmentioning
confidence: 99%